2020
DOI: 10.1111/1440-1630.12653
|View full text |Cite
|
Sign up to set email alerts
|

Learned pacing for adults with chronic pain: A randomised controlled trial feasibility study

Abstract: Chronic pain is a significant public health issue, with approximately 30% of the population worldwide reporting its presence (Elzahaf, Tashani, Unsworth, & Johnson, 2012). In 2018, this equated to 3.24 million Australians who were living with chronic pain (Deloitte Access Economics, 2019). The economic burden associated with chronic pain in Australia in 2018 was $73.2 billion dollars (Deloitte Access Economics, 2019). Chronic pain can be defined as pain that has not resolved within the expected timeframe of 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Given these findings, guideline recommendations urge clinicians to maximize nonpharmacologic and non-opioid therapies before considering opioid-based approaches [10,11]. Many nonpharmacologic treatment methods, such as lifestyle redesign programs, learned pacing, and energy conservation techniques, amongst other integrative and complementary approaches, have demonstrated significant and consistent longterm improvements in pain and function with minimal risk for harm [28][29][30][31][32].…”
Section: Chronic Pain Management Best Practice Recommendationsmentioning
confidence: 99%
“…Given these findings, guideline recommendations urge clinicians to maximize nonpharmacologic and non-opioid therapies before considering opioid-based approaches [10,11]. Many nonpharmacologic treatment methods, such as lifestyle redesign programs, learned pacing, and energy conservation techniques, amongst other integrative and complementary approaches, have demonstrated significant and consistent longterm improvements in pain and function with minimal risk for harm [28][29][30][31][32].…”
Section: Chronic Pain Management Best Practice Recommendationsmentioning
confidence: 99%
“…Neither pacing intervention significantly improve pain, fatigue, and self-reported physical disability compared to usual care. Three pilot trials have revealed mixed findings (Guy et al, 2020;Murphy et al, 2012;Racine et al, 2019;Schepens et al, 2012). Researchers have suggested that pain intensity may not be the most appropriate outcome measure to evaluate activity pacing interventions (Thompson, 2018) and have advocated for research to optimize how a pacing intervention is delivered and evaluated (Murphy et al, 2016;Racine et al, 2019).…”
Section: Introductionmentioning
confidence: 99%